DAMPAK PROFESI GURU TERHADAP TINGKAH LAKU ANAK DI SMA NEGERI 10 BATANGHARI KECAMATAN MUARA BULIAN KABUPATEN BATANGHARI - Soeraya, Titie Riski (Pendidikan Sosiologi, 2014)
The purpose of this research is to describe the effect of the teachers profession to the students behavior in SMA 10 Batanghari Kabupaten Batanghari. The theory used in this research is structural functionalism. This theory studied about the effect or the structure and function of social institutions in social life orderly and stable. Every social phenomeno has resulted from an objective, whether positive or negative. This research is categorized into types of qualitative research approaches. The types of this research used descriptive research. The number of informants as many as 23 people, consisting of 12 students and 11 parents, the informant criteria; 1) students whose parents are teachers, and 2) the elderly woman who worked as a student teacher. Data to be collected in this research are primary and secondary data obtained through the data collection methods such as interviews. The unit of analysis is the group with the analysis of the data comprising the steps of reduction, data presentation / analysis of data, and conclusions. The results of the effect of this research toward teaching profession to the studentâs behavior includes: 1) positive effect on the teaching profession to the studentâs behavior, which the teacher is a profession to educate or teach someone to be a good effect at the home, such as: a) forming a studentss behavior, b) to help the students in learning difficulties, and c) to make the students more diligent in learning. 2) The negative effect of teacherâs profesion toward the students behavior, it is to decrease time to communicate or gather with their the students, and the students would feel pressured by the predicate as the students at the school of teachers that will result in the students behavior, such as: a) do not come to school and b) lazy to study.